Analog Circuit Design High-Speed A-D Converters, Automotive Electronics and Ultra-Low Power Wireless - van Roermund, Arthur H.M; Casier, Herman; Steyaert, Michiel (Springer Netherlands : Imprint: Springer, 2006)
Analog Circuit Design contains in total 18 tutorials. They reflect the contributions of 6 experts in each of the three fields covered by the three chapters mentioned in the subtitle, as presented at the 15th workshop on Advances in Analog Circuit Design (AACD) held in Maastricht, April 2006. This book is number 15 in this successful series of Analog Circuit Design, providing valuable information and excellent overviews of analog circuit design and related CAD, mainly in the fields of basic analog modules, mixed-signal electronics, AD and DA converters, RF systems, and automotive electronics. Analog Circuit Design is an essential reference source for analog circuit designers and researchers wishing to keep abreast with the latest developments in the field. The tutorial coverage also makes it suitable for use in an advanced design course.